Early and Long-term Oncological Outcomes After Laparoscopic Resection for Colorectal Liver Metastases: A Propensity Score-based Analysis. Issue 5 (November 2015) - Allard, Marc-Antoine; Cunha, Antonio Sa; Gayet, Brice; Adam, René; Goere, Diane; Bachellier, Philippe; Azoulay, Daniel; Ayav, Ahmet; Navarro, Francis; Pessaux, Patrick
Abstract : Objective: To compare early and long-term outcomes in patients undergoing resection for colorectal liver metastases (CLM) by either a laparoscopic (LA) or an open (OA) approach. Background: The LA is still a matter of debate regarding the surgical management of CLM. Methods: Data of all patients from 32 French surgical centers who underwent liver resection for CLM from January 2006 to December 2013 were collected. Aiming to obtain 2 well-balanced cohorts for available variables influencing early outcome and survival, the LA group was matched 1:1 with the OA group by using a propensity score (PS)-based method. Results: The unmatched initial cohort consisted of 2620 patients (LA: 176, OA: 2444). In the matched cohort for operative risk factors (LA: 153, OA: 153), the LA group had shorter hospitalization stays [11.1 (±9) days vs 13.9 (±10) days; P  = 0.01] and was associated with lower rates of grade III to V complications [odds ratio (OR): 0.27, 95% confidence interval (CI) 0.14–0.51; P  = 0.0002] and inhospital transfusions (OR: 0.33 95% CI 0.18–0.59; P  < 0.0001). On a prognostic factors well-balanced population (LA: 73, OA: 73), the LA group and the OA group experienced similar overall (OS) and disease-free (DFS) survival rates [OS rates of 88% and 78% vs 84% and 75% at 3 and 5 years, respectively ( P  = 0.72) and DFS rates of 40% and 32% vs 52% and 36% at 3 and 5 years, respectively ( P  = 0.60)]. Conclusions: In the patients who are suitable for LA, laparoscopy yields better operative outcomes without impairing long-term survival. Abstract : Supplemental Digital Content is available in the text